NATO TRANSPORT THROUGH A “SCHENGEN MILITARY ZONE” FROM AN INTERNATIONAL LEGAL PERSPECTIVE - Jacek BARCIK; Piotr CZECH (Scientific Journal of Silesian University of Technology. Series Transport)
The cross-border transport of soldiers and military equipment is particularly difficult and characterized by a distinct difference with civil transport. For its implementation, political will is needed, in line with the tolerance of representatives of foreign armed forces on the territory of the state, as well as adequate transport capacity and infrastructure capable of ensuring transport efficiency. These circumstances are particularly important in the case of alliance cooperation within NATO in the Euro-Atlantic subregion. Legislation within the organization is designed to ensure coordination of military transport activities. However, the procedures currently in place are criticized as being too rigid and failing to provide a quick transfer of forces and resources in the event of a sudden threat to one of NATO’s allies. For this reason, there have been calls to create an allied “Schengen military zone”, in which the Schengen Agreement would be abolished, internal controls and administrative hindrances between NATO countries would be lifted, and the free transport of soldiers and military equipment would take place. The aim of this article is to examine the feasibility of implementing this proposal and to identify the basic difficulties involved in carrying out military transport within the NATO context. A question arises about the possibility of creating a “Schengen military zone” for NATO. The aim of the article is, firstly, to present NATO legal sources governing the issue of military transport. In the next part of the analysis, allied military transport procedures will be analysed, accompanied by a critical identification of potential shortcomings. The article concludes by providing answers to the research question.